Hunting for leopards : long run country income dynamics in Africa - Arbache, Jorge Saba (Policy research working paper, 2008)
"This paper examines the country-level dynamics of long-run growth in Africa between 1975 and 2005. The authors examine how growth has affected mobility and the distribution of income among countries. They analyze changes in cross-country income structure and convergence, and look for evidence of the formation of country groups or "clubs." Using a novel method of breaking up the growth histories of African economies into medium-term spells of growth accelerations and declines, the authors investigate whether a group of African "leopards" - the regional equivalent of Asia's "tigers" - is beginning to emerge. "--World Bank web site